The Influence of Environmental Awareness, Price, and Digital Marketing on Green Product Purchase Decisions: A Case Study on Students of Dian Nusantara University - Achmad Tarmizi; Shieto, Shieto (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study investigates the influence of environmental awareness, price, and digital marketing on green product purchase decisions among students at Dian Nusantara University. The research uses a quantitative method, employing questionnaires distributed to 200 respondents. The data were analyzed using multiple linear regression. The results demonstrate that all three variables—environmental awareness, price, and digital marketing—have a significant positive effect on green product purchase decisions. Environmental awareness emerged as a key motivator, while price influenced consumer choices based on perceived value. Digital marketing played a dominant role in shaping awareness and purchase behavior. The findings highlight the importance of integrating eco-conscious values with effective pricing strategies and digital engagement to foster green consumption. This study provides both theoretical insights and practical recommendations for marketers and policymakers seeking to promote sustainable consumer behavior among the younger generation.